2009
DOI: 10.1267/ahc.09019
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exercise-induced Fatigue on Acetylcholinesterase Expression and Activity at Rat Neuromuscular Junctions

Abstract: Acetylcholinesterase is the enzyme that terminates neurotransmission by hydrolyzing the acetylcholine released by the motoneurons at the neuromuscular junctions. Although acetylcholinesterase has been studied for almost a century, the underlying relationship between exercise-induced fatigue and acetylcholinesterase activity at the synaptic cleft is not clear. The purpose of this study was to assess the effects of exercise-induced fatigue on the expression and activity of acetylcholinesterase at the neuromuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
9
2
3
Order By: Relevance
“…In contrast, exercise can decrease AChE activity [35]. In the current study, the results show that the exercised EC, EA, and ET groups tended to have increased brain AChE activity, but that the differences were not significant.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, exercise can decrease AChE activity [35]. In the current study, the results show that the exercised EC, EA, and ET groups tended to have increased brain AChE activity, but that the differences were not significant.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, there were small sized neuromuscular junction (NMJ) areas. The intensity of AChE staining reflects its activity as reported by Wen et al, [31]. While Liu et al, [33] suggested that the density of AChE staining reflects the amount of AChE in the NMJ and the size of the AChE-positive region reflected the size of the NMJ.…”
Section: The Morphometric Resultsmentioning
confidence: 78%
“…It rapidly hydrolyzes acetylcholine released from the nerve terminals [30]. It is well established that AChE activity is also influenced by the pattern of nerve impulses, muscle electromechanical activity and neurogenic substances conveyed by axonal transport [31]. The levels of AChE mRNA decrease following skeletal muscle denervation [32].…”
Section: The Morphometric Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurotransmitter depletion 814 and the associated synaptic fatigue 1522 may contribute to chronic pain states. Neurotransmitter depletion results from an increase in precursor turnover and dietary deficiency of the precursor.…”
Section: Introductionmentioning
confidence: 99%